2012
DOI: 10.1016/j.jmii.2012.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Activities of doripenem against nosocomial bacteremic drug-resistant Gram-negative bacteria in a medical center in Taiwan

Abstract: Doripenem was as effective as imipenem and meropenem in our study. However, there was a significant proportion of carbapenem resistance among the tested isolates. Hence, longitudinal surveillance is necessary to monitor the resistance trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…In a previous study that investigated the in vitro activity of doripenem in antibiotic-resistant clinical isolates collected from 2001-2002, doripenem was more potent than imipenem or meropenem even against non-fermentative GNB [ 19 ]. However, more recent studies of blood GNB isolates reported that doripenem and other carbapenems had similar in vitro activity against non-fermentative GNB, similar to the results of our study [ 11 12 ]. Thus, doripenem should not be considered a treatment option against imipenem-or meropenem-resistant non-fermentative GNB blood isolates, or against hospital-acquired infections or pneumonia in which these GNB isolates are suggested as likely pathogens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a previous study that investigated the in vitro activity of doripenem in antibiotic-resistant clinical isolates collected from 2001-2002, doripenem was more potent than imipenem or meropenem even against non-fermentative GNB [ 19 ]. However, more recent studies of blood GNB isolates reported that doripenem and other carbapenems had similar in vitro activity against non-fermentative GNB, similar to the results of our study [ 11 12 ]. Thus, doripenem should not be considered a treatment option against imipenem-or meropenem-resistant non-fermentative GNB blood isolates, or against hospital-acquired infections or pneumonia in which these GNB isolates are suggested as likely pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, doripenem, the latest introduced agent of the carbapenem class, may be a useful alternative treatment option as it shows potent in vitro antimicrobial activity against MDR-GNB and clinical effectiveness comparable with other carbapenems [ 5 6 7 8 9 ]. However, clinicians are usually reluctant to prescribe doripenem, because data regarding doripenem susceptibility are rarely available from widely used automated susceptibility testing panels [ 10 ] and the in vitro activity of doripenem against clinically significant isolates such as blood isolates has not been reported separately in the context of recent increases in carbapenem resistance, except for a few studies [ 11 12 ]. One included only blood isolates from bacteremic urinary tract infections, and the other did not include distinct clinical information on bacteremia cases.…”
Section: Introductionmentioning
confidence: 99%
“…Because most automated susceptibility testing panels [10] do not include doripenem, and knowledge about the in vitro activity of doripenem against clinically isolated pathogens in the context of increasing carbapenem resistance is limited [11,12], clinicians usually more frequently prescribe imipenem or meropenem rather than doripenem in clinical practice. Thus, data regarding the clinical experience of patients receiving doripenem are limited.…”
Section: Introductionmentioning
confidence: 99%
“…В то же время в исследовании in vitro, проведенном S.X. Dong et al, активность этих трех карбапенемов была одинаковой: чувствительны к дорипенему, имипенему и меропенему были 56, 60 и 60% штаммов соответственно при МИК 50 меньше 0,5 мкг/мл [21].…”
Section: антимикробная активность дорипенема In Vitro в отношении оснunclassified